Use of fibre waste as a binder - I. L. Chulkova; I. A. Selivanov (Вестник СибАДИ, 2021)
Introduction. The need for a more efficient and varied use of waste from the pulp and paper industry dictates the need to search for new directions for the use of such waste in construction materials science technologies.Materials and methods. In the studies the fibre waste of the Perm Cardboard LLC company with a moisture content after washing of 300% by weight was used. Currently, many issues of theory and practice the production of materials from the fibre waste are not entirely solved, resulting in a number of provisions borrowed from the theory of the production of concrete mineral aggregates, as well as the production of pulp and paper industry.Results. Due to its chemical and material composition, the possibility of using the fibre waste in construction materials science technologies as an independent air binder is shown. The studies have established that the initial moisture content of the fibre waste as a binder affects the final quality indicators of a dry material. Thus, the lowest dry material density of 350 kg/m3 is observed at the initial humidity of the mixture in the range of 650% by weight. At a density of 350 kg/m3, the hygroscopicity of the material is 4.3%, the shrinkage from 10 to 25%. The drying time of the product is within 11 hours. A leveling high shrinkage is achieved by introducing light aggregates with a rough surface during the molding process.Discussion and conclusions. The obtained data on the structure, the composition of the fibre waste, as well as the dependence and regularities of the behavior of a highly concentrated dispersed system of the ‘fibre waste-water’ type show the possibility of using the fibre waste for the production of thermal insulation materials, both as a main component and in a composition with aggregates as an independent air binder. At the same time, the final density indicators of thermal insulation products are within the limits established by regulatory documents.